Experimental and numerical investigation of the effect of turbulent inflow on a Horizontal Axis Wind Turbine (part II: Wake characteristics). (15th October 2016) - Li, Qing'an; Murata, Junsuke; Endo, Masayuki; Maeda, Takao; Kamada, Yasunari
Abstract: The wake of a wind turbine is the driving phenomenon for wind velocity recovery in a wind farm and for the interaction between wind turbines. The objective of this research was to present the turbulent wake characteristics of the Horizontal Axis Wind Turbine (HAWT) by comparing the results between the model fitted and wind tunnel experiments. In wind tunnel experiments, the wind velocities of wind turbine wake were investigated by a hot wire anemometer at different turbulence intensities and wind shears. Then, in order to verify the accuracy of wind turbine wake, wind velocity distribution in the wake was evaluated quantitatively by wake model using Gaussian function. By comparing the results of wind tunnel experimental and numerical analysis, it was found that recovery of wind velocity and expansion of wake deficit area were promoted by turbulence of inflow which was generated by active turbulence grids. Moreover, wake distribution of model agreed well with experimental results in the far-wake region. Highlights: Active turbulence grids and atmospheric boundary layer generation device were used. Wake velocity was measured at different turbulence intensities and wind shears. Wind velocity deficit region was promoted in the upper layer. Optimum pitch angle β was different at different wind shear exponents. Higher turbulence intensity promoted the expansion of wake deficit area.